Selective deforestation and exposure of African wildlife to bat-borne viruses - Fedurek, Pawel; Asiimwe, Caroline; Rice, Gregory K.; Akankwasa, Walter J; Reynolds, Vernon; Hobaiter, Catherine; Kityo, Robert; Muhanguzi, Geoffrey; Zuberbühler, Klaus; Crockford, Catherine; Cer, Regina Z; Bennett, Andrew J; et al. (Nature Publishing Group UK, 2024)
Proposed mechanisms of zoonotic virus spillover often posit that wildlife transmission and amplification precede human outbreaks. Between 2006 and 2012, the palm Raphia farinifera , a rich source of dietary minerals for wildlife, was nearly extirpated from Budongo Forest, Uganda. Since then, chimpanzees, black-and-white colobus, and red duiker were observed feeding on bat guano, a behavior not previously observed. Here we show that guano consumption may be a response to dietary mineral scarcity and may expose wildlife to bat-borne viruses. Videos from 2017–2019 recorded 839 instances of guano consumption by the aforementioned species. Nutritional analysis of the guano revealed high concentrations of sodium, potassium, magnesium and phosphorus. Metagenomic analyses of the guano identified 27 eukaryotic viruses, including a novel betacoronavirus. Our findings illustrate how “upstream” drivers such as socioeconomics and resource extraction can initiate elaborate chains of causation, ultimately increasing virus spillover risk. A study in Uganda found that local extirpation of a mineral-rich tree species used in tobacco farming forced wildlife to obtain minerals by eating bat guano, in which 27 eukaryotic viruses were identified, including a novel betacoronavirus.
Keywords: deforestation; African wildlife; bat-borne viruses